Anatomical and computed tomography study of the eighth costochondral junction: topography for costochondral graft harvesting. - Lepage, D.; Tatu, L.; Loisel, F.; Rey, P.; Obert, L.; Parratte, B. (Surgical & Radiologic Anatomy, 2016)
Introduction: Costochondral grafts have long been used in maxillofacial reconstruction, but have been little used in trauma and orthopedic cases. This surgical technique requires that a graft be harvested from the thorax in the area of the eighth rib. Pleuropulmonary complications are very rare. Although the harvesting technique is simple, it needs to be demystified. Goal of study: This study was performed to define anatomical relationships in the eighth costochondral junction and identify topographical and anatomical landmarks that will make it easier to harvest this structure. Method: This was a two-part study. First, an anatomical study was carried out on human cadaver thoraxes to define topographical landmarks and study the anatomical surroundings of the eighth costochondral junction. Second, an imaging study was performed using a database of existing patient computed tomography (CT) scans of the chest and abdomen to confirm the topographical landmarks defined in the first part of the study. The spine was used as a reference for both studies. The location of the eighth costochondral junction was defined relative to the spinal processes along with its location on the lower rib cage hemiperimeter in the transverse plane starting at the corresponding spinous process. Results: The eighth costochondral junction was in line with the spinal process of the twelfth thoracic vertebra in the vast majority of cases and located at two-thirds of the lower rib cage hemiperimeter from the posterior median sulcus, regardless of the patient's chest shape, age and gender. This junction was always located under a single muscle (external oblique) and protected by a thick perichondrium layer, which separates it from the intercostal pedicles, endothoracic fascia and parietal pleura. Discussion: This two-part study has identified reliable landmarks for harvesting of an osteochondral graft at the eighth costochondral junction and, by describing its anatomical surroundings, helps take the mystery out of its harvesting. These landmarks were identified in supine cadavers and in free-breathing patients lying in supine for the CT portion. This position must be used when identifying these landmarks in a patient undergoing costochondral autograft harvesting for cartilage reconstruction.